2018
DOI: 10.3390/nu10070928
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet and Serum Adiponectin Levels in Pregnancy: Results from a Cohort Study in Normal Weight Caucasian Women

Abstract: The Mediterranean Diet (MedDiet) is significantly associated with anti-inflammatory effects and a favorable health outcome. During pregnancy, both inflammatory changes and oxidative balance are essential for a successful outcome, while an unbalanced inflammatory response can be a key mediator of obstetrical syndromes. The aim of this study is to investigate the adherence to MedDiet during pregnancy in the 1st and in the 3rd trimester, and to test whether the adherence was associated with serum adiponectin leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 35 publications
0
55
0
Order By: Relevance
“…It is difficult to explain whether changed levels of adipokines are directly associated with diet. Some authors suggested that polyphenols, vitamins, and fiber derived from plant-based foods are the main bioactive compounds that are associated with the anti-inflammatory and antioxidant properties [ 57 , 58 , 59 ]. It is not excluded that a lower dietary intake of total protein and animal protein, but a higher intake of plant protein and fiber observed in vegetarians may have a direct beneficial effect on body composition, fat tissue secretion, lipid profile, and glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to explain whether changed levels of adipokines are directly associated with diet. Some authors suggested that polyphenols, vitamins, and fiber derived from plant-based foods are the main bioactive compounds that are associated with the anti-inflammatory and antioxidant properties [ 57 , 58 , 59 ]. It is not excluded that a lower dietary intake of total protein and animal protein, but a higher intake of plant protein and fiber observed in vegetarians may have a direct beneficial effect on body composition, fat tissue secretion, lipid profile, and glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal circulating HMW adiponectin and HMW/total adiponectin ratio are lower in late gestation than in the nonpregnancy period, but there is no significant difference in circulating adiponectin multimers between the early and late pregnancy periods . Adiponectin levels correlate inversely with gestational age in normal‐weight pregnant women but not in overweight women and, in the third trimester, fall significantly as compared with the levels in the first trimester . The increase in maternal fat deposition during the progression of pregnancy, the inverse relationship between adiponectin and body fats, and the downregulation of adiponectin by increased fat mass explain this observation.…”
Section: The Physiological Profile Of Adiponectin During Normal Pregnmentioning
confidence: 94%
“…In total, 27 observational studies were included in the review: 17 (63.0%) cohort studies [20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36][37]; 7 (25.9%) cross-sectional studies [38][39][40][41][42][43][44]; 2 (7.4%) case-control studies [23,45]; and, 1 (3.7%) nested case-control study [46]. Table 2 provides a summary of the key characteristics of these 27 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Moreover, nine studies grouped fruits and nuts together as a single component [21,22,24,[27][28][29][30]37,39] in line with the original designs of the MDS-2003 [13] and rMed [49] employed by these studies. [20][21][22][23][24][27][28][29][30][32][33][34]36,37,[39][40][41][42][43][44][45][46], including only the PREDIMED score of Martínez-Galiano et al (2018) [23]. Thirteen studies categorized nuts as a separate component from fruits [20,23,[32][33][34]36,[40][41][42][43][44][45][46].…”
Section: Fruitsmentioning
confidence: 99%